Mixue Expansion Strategy: The Effect of Location, Price, Lifestyle on Purchasing Decision and Brand Image As Intervening - Aloysius Rangga Aditya Nalendra; Slamet Heri Winarno; Agus Priadi (Jurnal Manajemen dan Kewirausahaan, 2023)
For culinary service providers, especially soft drinks (ice cream) today, knowing the pattern of buying decisions of consumers is very important. Efforts need to be made to create an expansion strategy so that products can be recognized and consumed by consumers. Mixue as one of these business actors has succeeded in running its business during fierce competition. The Mixue network now spreads throughout all regions in Indonesia as a result of its success in implementing business strategies. This study aims to examine the factors that can influence the decision to purchase Mixue products such as location, price, lifestyle, and brand image as intervening variables as a means of implementing a business expansion strategy. The subjects of this study were Mixue connoisseurs who live in Central Jakarta with a sample size of 150 respondents using a simple random sampling technique. The data analysis method uses causative quantitative analysis using SEM analysis. The results showed that the location variable dominantly influences purchasing decisions, this proves that Mixue's expansion strategy is focused on increasing Mixue outlets that are affordable to the public, followed by the price variable. The role of brand image is believed to be a determining factor in the expansion strategy as a determinant of indirect influence.